Unambiguous Determination of Benzo[a]pyrene and Dibenzo[a,l]pyrene in HPLC Fractions via Room-Temperature Fluorescence Excitation–Emission Matrices - Knecht, George T. (2025)
When high-performance liquid chromatography (HPLC) is used for the analysis of polycyclic aromatic hydrocarbons (PAHs) in complex samples, further examination of HPLC fractions is recommended to confirm PAH assignments solely based on retention times. Gas chromatography–mass spectrometry (GC-MS) has been particularly relevant in the unambiguous determination of PAHs with remarkably similar retention times. The combination of HPLC and GC requires lengthy analysis times to ensure proper assignments. This article presents an approach for the analysis of co-eluted PAHs with no need for further chromatographic separation. Benzo[a]pyrene (BaP) and dibenzo[a,l]pyrene (DBalP) were directly determined in a co-eluted HPLC fraction via room-temperature fluorescence excitation–emission matrices (RTF-EEMs). RTF-EEMs can be recorded in a matter of seconds with a spectrofluorometer equipped with a multichannel detection system. The spectral overlapping of BaP and DBalP was resolved using parallel factor analysis (PARAFAC). The analytical advantages of this approach were demonstrated with the trace analysis (ng/mL) of these two PAHs in pre-concentrated tobacco extracts.